Bankruptcy Analysis as a Basis for Discontinuous Termination of Notaries - Amira Ulfah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
A notary is a public official authorized to do authentic deeds and has other authorities referred to in Law Number 30 of 2004. In light of this, the author concludes that Article 12 letter a of Law Number 30 of 2004 concerning the Position of a Notary contains a legal ambiguity. As a result, the authors are interested in investigating bankruptcy as a reason for a notary's dishonourable dismissal. In terms of data, this study relies on qualitative. However, from the results and discussion above, it can be concluded that the Notary is classified as an individual legal subject rather than a legal entity under bankruptcy law. So, suppose a Notary is declared bankrupt. In that case, he or she loses only their authority to manage assets listed in the bankruptcy register, but not their position. Therefore, due to bankruptcy decisions, notaries cannot be dishonourably dismissed from their positions.